Les Dynastes de Thomas Hardy : une poétique spectrale à l’œuvre contre la guerre - Annie Escuret (Cahiers Victoriens et Edouardiens)
The aim of this paper is to examine Hardy’s poetic magnum opus, The Dynasts, as a spectro-poetics against war. The effect of the spectral representation has often been noted but we need a contemporary outlook to understand the role of « spectres ». The living-dead, the phantom, the spectre appear in Derrida’s Specters of Marx (1993) but these concepts also appear in Freud’s notion of « The Uncanny », Foucault’s categories of silence and unspeakability or Kristeva’s definition of the abject. In The Dynasts, Hardy wrote an epic of human automatism or impulsion, an account of human action in spite of human knowledge which is a most violent indictment of war showing that Hardy heralds modern pacifists like Michel Serres or René Girard.